Comparison conventional endoscopic myringoplasty with fibrin glue supplemented endoscopic myringoplasty - Rajendiran Devendiran; Nagabooshanam Mohanbabu; Venugopal Ravikumar (MGM Journal of Medical Sciences, 2022)
Introduction: The fibrin tissue glues have been used in many surgeries to reinforce surgical sutures and tissue adhesion. Myringoplasty is the commonly done ear surgery for the perforations of the tympanic membrane, where no suturing is done between remnant membrane and graft. Aim: The aim of the study is to compare the results and effectiveness of this biological fibrin tissue glue in myringoplasty surgeries as a supplementary procedure to conventional endoscopic myringoplasty (CEM) surgeries. Materials and Methods: Seventy patients with chronic suppurative otitis media with tympanic membrane perforation without ossicular and mastoid involvement have been chosen. One group of 35 patients underwent CEM surgeries. In another group of 35 patients, biological fibrin tissue glue, TISSEEL, has been used as supplementary to the CEM surgeries, and the graft uptake rate and hearing improvement were evaluated and compared postoperatively. Results: The graft success rate at 3 months postoperatively was 91.42% in both the groups, that is, 32/35, and these values were not statistically significantly different (P = 1.00). There was a highly statistically significant hearing outcome before and after the surgery in both the CEM and the fibrin tissue glue supplemented endoscopic myringoplasty groups. However, there was no statistically significant change in hearing outcomes between the two groups. Conclusion: In our study, we have got more or less similar results compared with the results of the studies on routine CEM cases. But the high-cost nature of the commercially available fibrin tissue glue makes it difficult to recommend for use in all routine endoscopy myringoplasty cases.